Classification of patients who experience a higher distress level to transoral esophagogastroduodenoscopy than to transnasal esophagogastroduodenoscopy. Issue 4 (17th December 2012) - Miyake, Kazumasa; Kusunoki, Masafumi; Ueki, Nobue; Yamada, Akiyoshi; Nagoya, Hiroyuki; Kodaka, Yasuhiro; Shindo, Tomotaka; Kawagoe, Tetsuro; Gudis, Katya; Futagami, Seiji; Tsukui, Taku; Sakamoto, Choitsu
<x xml:space="preserve">Abstract</x> Background In Japanese routine clinical practice, endoscopy is generally carried out without sedation. The present study aimed to identify the factors essential for appropriate selection of transnasal esophagogastroduodenoscopy (TN‐EGD) as an alternative to unsedated transoral esophagogastroduodenoscopy (TO‐EGD). Patients and methods Subjects in this prospective cohort study comprised consecutive outpatients who underwent EGD at a single center. Factors predicting TO‐EGD‐induced distress were evaluated on a visual analog scale (VAS) and analyzed. Patients were classified into a two‐layered system on the basis of these predictive factors, and the severity of distress between the TN‐EGD and TO‐EGD groups was compared using VAS and the change in the rate–pressure product as subjective and objective indices, respectively. Results In total, 728 outpatients (390 male, 338 female; mean age, 63.1 ± 0.5 years; TO‐EGD group, 630; TN‐EGD group, 98)met the inclusion criteria. Multivariate logistic regression analysis confirmed that age <65 years (P < 0.01; odds ratio [OR], 1.69; 95% confidence interval [CI], 1.14–2.52), gender (female; P < 0.01; OR, 1.97; 95% CI, 1.34–2.91), marital status (single; P < 0.01; OR, 1.96; 95% CI, 1.18–3.27), and anxiety towards TO‐EGD (P < 0.001; OR, 3.62; 95% CI, 2.44–5.37) were independently associated with intolerance. Both indices were significantly higher in the TO‐EGD subgroup than in the TN‐EGD subgroup in the high predictive class, but not in the low predictive class. Conclusion Predictive factors for detecting intolerance to unsedated TO‐EGD may be useful to appropriately select patients who transpose unsedated TO‐EGD to TN‐EGD.